Nano-chitosan coating on maintaining the quality of postharvest chili pepper (Capsicum frutescens L.) - Noor Laila Safitri; Erma Prihastanti; Sri Widodo Agung Suedy; Agus Subagio (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Chili pepper (Capsicum frutescens L.) is a horticulture product with a limited shelf life due to quality degradation following harvest. One method of preserving the quality of chili peppers can be evaluated by using nano-chitosan, which combine chitosan and sodium tripolyphosphate (STPP) in certain ratio. The purpose of this study was to determine the impact of nano-chitosan on maintaining the quality of C. frutescens L., the optimal ratio of chitosan to STPP for preserving the quality of C. frutescens L. after harvest, and the shelf life of C. frutescens L. treated with nano-chitosan after harvest. This study employed a completely randomized design (CRD) and included four treatments: P0 (control), P1 (0.2% nano-chitosan, 1:3 ratio), P2 (0.2% nano-chitosan, 1:4 ratio), and P3 (0.2% nano-chitosan, 1:5 ratio), which conducted for 16 days. Weight loss, water content, texture, color, and percentage of damage are the research variables in this study. The ANOVA test was used to examine the data, followed by the DMRT test. The results indicated that nano-chitosan could maintain the weight, water content, texture, and color of chili peppers. The optimal ratio of chitosan to STPP to retain the quality of postharvest C. Frutescens L. is 0.2% nano-chitosan (chitosan: STPP= 1:5), and nano-chitosan can maintain the quality of C. Frutescens L. for up to 16 days.